Investigation of Isolation Approaches and the Stoichiometry of SiNx Passivation Layers in "Buffer‐Free" AlGaN/GaN Metal–Insulator–Semiconductor High‐Electron‐Mobility Transistors. Issue 8 (11th December 2022) - Hult, Björn; Thorsell, Mattias; Chen, Jr-Tai; Rorsman, Niklas
Abstract : Critical process modules for the fabrication of metal–insulator–semiconductor high‐electron‐mobility transistors (MISHEMTs) based on a novel 'buffer‐free' AlGaN/GaN heterostructure grown with metal–organic chemical vapor deposition (MOCVD) are presented. The methods of isolation and passivation for this type of heterostructure are investigated. Utilizing nitrogen implantation, it is possible to achieve off‐state destructive breakdown voltages (BVs) of 2496 V for gate–drain distances up to 25 μm, whereas mesa isolation techniques limit the BV below 1284 V. The stoichiometry of the SiN x passivation layer displays a small impact on the static and dynamic on‐resistance. However, MISHEMTs with Si‐rich passivation show off‐state gate currents in the range of 1–100 μA mm −1 at voltages above 1000 V, which is reduced below 10 nA mm −1 using a stoichiometric SiN x passivation layer. Destructive BVs of 1532 and 1742 V can be achieved using gate‐integrated and source‐connected field plates for MIHEMTs with stoichiometric and Si–rich passivation layers, respectively. By decreasing the field plate lengths, it is possible to achieve BVs of 2200 V. This demonstrates the implementation of MISHEMTs with high‐voltage operation and low leakage currents on a novel "buffer‐free" heterostructure by optimizing the SiN x stoichiometry. Abstract : Herein, a 'buffer‐free' high‐voltage GaN‐on‐SiC metal–oxide–semiconductor high‐electron‐mobility transistor (MISHEMT) is demonstrated. Using nitrogen implantation isolation, a high breakdown voltage of 2496 V can be achieved. Off‐state leakage currents below 100 nA mm −1 can also be demonstrated without compromising dynamic performance in the measured interval utilizing a stoichiometric SiN x passivation layer and gate dielectric.